Autoantibody to MDM2: A Potential Serological Marker of Systemic Lupus Erythematosus - Yuan Liu; Liping Dai; Weihong Liu; Guixiu Shi; Jianying Zhang (Journal of Immunology Research)
Introduction. Systemic lupus erythematosus (SLE) is one of the systemic autoimmune diseases characterized by the polyclonal autoantibody production. The human homologue of the mouse double minute 2 (MDM2) is well known as the negative regulator of p53. MDM2 has been reported to be overexpressed in SLE animal model and to promote SLE. Since abnormally expressed proteins can induce autoimmune response, anti-MDM2 autoantibody was examined in SLE patients. Methods. Anti-MDM2 antibody in sera from 43 SLE patients and 69 healthy persons was investigated by ELISA. Positive samples were further confirmed by western blotting. The immunological feathers of anti-MDM2 positive sera were analyzed by indirect immunofluorescence assay. Anti-p53 was also investigated in SLE patients by ELISA, and the correlation of anti-MDM2 and anti-p53 was analyzed. Results. The presence of anti-MDM2 in SLE patients was 23.30%, much higher than normal healthy persons (4.30%). These anti-MDM2 positive sera present a nuclear staining pattern. The presence of anti-p53 in SLE patients was 39.50%, and the titer of anti-MDM2 was positively correlated with anti-p53 in SLE patients. Conclusions. Anti-MDM2 autoantibody was detected at high prevalence in SLE patients. The detection of anti-MDM2 in SLE patients should be clinically useful.